2020
DOI: 10.1002/app.49803
|View full text |Cite
|
Sign up to set email alerts
|

Improved chemical stability and proton selectivity of semi‐interpenetrating polymer network amphoteric membrane for vanadium redox flow battery application

Abstract: In this work, semiinterpenetrating polymer network (semi-IPN), consisting of sulfonated poly (arylene ether sulfone) (SPAES) and crosslinked vinyl imidazole grafted polysulfone (VMPSU), is prepared and characterized. FTIR, EDS, and solubility test indicate the successful preparation of amphoteric membranes. The semi-IPN amphoteric membranes exhibit better stability than pure SPAES membrane, as demonstrated by thermogravimetric analysis and ex situ immersion testing results. More importantly, it is shown that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…The surface and cross-section morphology of all the membranes were observed by scanning electron microscopy (SEM), which is shown in Figure . It can be clearly seen that the surfaces of all the membranes (Figure a–f) exhibit homogeneous and smooth morphologies, which is attributed to the excellent compatibility between OPBI and Co-BPPBI, since they have similar aromatic frameworks . Moreover, with increasing the concentration of bipyridine group in the copolymer the cross-section morphology of copolymers demonstrates the characteristics of tough polymers (Figure a 1 -d 1 ).…”
Section: Resultssupporting
confidence: 88%
“…The surface and cross-section morphology of all the membranes were observed by scanning electron microscopy (SEM), which is shown in Figure . It can be clearly seen that the surfaces of all the membranes (Figure a–f) exhibit homogeneous and smooth morphologies, which is attributed to the excellent compatibility between OPBI and Co-BPPBI, since they have similar aromatic frameworks . Moreover, with increasing the concentration of bipyridine group in the copolymer the cross-section morphology of copolymers demonstrates the characteristics of tough polymers (Figure a 1 -d 1 ).…”
Section: Resultssupporting
confidence: 88%
“…The preparation of SPAES was similar to our previous study, 35 the synthesis procedure of SPAES was shown in Figure 1 and it could be described as following: DFDPS (6.0 mmol, 1.526 g), SDFDPS (6.0 mmol, 2.750 g), BPA (12.0 mmol, 2.739 g) and K 2 CO 3 (28.8 mmol, 3.980 g) were added into a 100 ml three-neck flask with condenser, gas adapter, mechanical stirrer and Dean-Stark trap. Then 24 ml NMP and 12 ml toluene were charged into the reactor under nitrogen atmosphere.…”
Section: Synthesis Of Spaesmentioning
confidence: 66%
“…The peaks at 1026 cm À1 and 1095 cm À1 are attributed to the stretching vibration of O¼S¼O of sulfonic acid group. 35…”
Section: Chemical Structure Evaluationmentioning
confidence: 99%
“…Currently, the Nafion® commercial membrane is widely used in VRFB. Nafion has high proton conductivity and excellent chemical stability; its high permeability to vanadium ions and high cost however prevent a wide commercial application of VRFB 4–6 . Therefore, alternative materials are under intense research.…”
Section: Introductionmentioning
confidence: 99%